2013
DOI: 10.1039/c3ta10531h
|View full text |Cite
|
Sign up to set email alerts
|

Room-temperature solution-processed molybdenum oxide as a hole transport layer with Ag nanoparticles for highly efficient inverted organic solar cells

Abstract: While metal oxide films are typically formed by high-temperature and sputtering processes, we report an approach with the features of a room-temperature, water-free and solution-based process for the formation of a molybdenum oxide (MoO x ) film for inverted organic solar cells (OSCs) by proposing a vacuum treatment at room temperature and selecting an appropriate solvent. Remarkably, our results indicate that the vacuum treatment can introduce oxygen vacancies in the molybdenum oxide film and modify its work … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
64
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 94 publications
(70 citation statements)
references
References 46 publications
3
64
0
2
Order By: Relevance
“…27,29,39,40 Molybdenum powder and vanadium powder were purchased from Aladdin Industrial Inc., Shanghai, China. For the molybdenum bronze solution, 0.1 g molybdenum metal powder was dispersed into 10 mL of ethanol using an ultrasound bath, followed by mixing 0.3 mL of hydrogen peroxide (H 2 O 2 ) (30%).…”
Section: Materials Synthesis and Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…27,29,39,40 Molybdenum powder and vanadium powder were purchased from Aladdin Industrial Inc., Shanghai, China. For the molybdenum bronze solution, 0.1 g molybdenum metal powder was dispersed into 10 mL of ethanol using an ultrasound bath, followed by mixing 0.3 mL of hydrogen peroxide (H 2 O 2 ) (30%).…”
Section: Materials Synthesis and Preparationmentioning
confidence: 99%
“…Recently, solution-processed metal oxides such as MoO 3 , V 2 O 5 , TiO 2 and SnO x with new features of low-temperature and cost-effective processing methods have been developed to improve the availability of organic optoelectronics to the general public. [24][25][26][27][28][29][30] Moreover, for instance, Cs-doped TiO 2 , Csdoped ZnO, Al-doped ZnO, Al-doped MoO 3 and metal oxides incorporated with other functional elements have been developed to realize efficient carrier transport with other features of high conductivity, the carrier blocking effect and optical enhancement. [31][32][33][34][35][36][37][38] These doped metal oxide interfacial layers require high-temperature annealing or co-evaporation methods, and the film formation is usually limited to either normal or inverted device architecture only.…”
Section: Introductionmentioning
confidence: 99%
“…The solution which composed of poly(3-hexylthiophene) (P3HT) and 6,6-phenyl-C61 butyric acid methyl ester (PCBM) in chlorobenzene with concentration of 25 mg/mL and 1:0.7 weight ratio was spin-coated at 850 rpm for 10 s to form the active layer. The devices were then pre-annealed on the hot plate at 110°C for reported previously [26]. The Ag electrode was deposited through a shadow mask to form active area of $4 mm 2 using thermal evaporator with a thickness of 100 nm at 3 Â 10 À6 Torr.…”
Section: Device Fabrication and Characterizationmentioning
confidence: 99%
“…Cheng et al [18] had shown matched energy level between E v of MoO 3 and HOMO of P3HT, which is beneficial for hole extraction. On the other hand, Li et al [10] considered hole transportation from HOMO of P3HT via Fermi level of MoO 3 to the anode. Hammond et al [19] presented that the MoO x HTL devices exhibited slightly reduced open circuit voltages and short circuit current densities with respect to the PEDOT:PSS OPV, likely due in part to charge recombination at Mo 5+ gap states in the HTL; however, the cell showed enhanced fill factors due to reduced series resistance (R s ) in the MoO x HTL.…”
Section: Introductionmentioning
confidence: 98%
“…Additionally, the hygroscopicity of PEDOT:PSS is not optimal for organic active layer [8]. Many transition metal oxides are studied to replace PEDOT: PSS, such as MoO 3 [9,10], V 2 O 5 [11], WO 3 [12] and NiO [13]. Recently, MoO 3 has recognized as an important HTL material because of its good ability of carrier transportation and better stability comparing to PEDOT:PSS [9,[14][15][16].…”
Section: Introductionmentioning
confidence: 99%